All Days 1993
DOI: 10.2118/25756-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Mechanics Issues Relating to Cuttings Re-Injection at Shallow Depth

Abstract: Re-injection of oil contaminated drill cuttings is attracting considerable attention as a cost effective means of complying with environmental legislation concerning discharges of drilling wastes. Gyda is the first North Sea platform to adopt this method as the sole means of disposing of its drilling wastes. The ground cuttings slurry (ca. 15,000 bbls per well) is injected via the 13 3/8" × 9 5/8" casing annulus into hydraulic fractures of up to 213m radius created in the mudstone formation at 900m depth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…These authors have demonstrated experimentally that the rate of fluid leakoff decreases with increase of fluid pressure due to cake compaction during the pumping stage, and the leakoff increases slightly due to filtercake relaxation during the closure stage. An experimental study [28] on propagation of hydraulic fracture in an underconsolidated porous rock has shown that the hole breakdown pressure and fracture propagation pressure are much higher than that predicted by the elastic analysis.…”
Section: Poroelasticity and Filtercakementioning
confidence: 86%
“…These authors have demonstrated experimentally that the rate of fluid leakoff decreases with increase of fluid pressure due to cake compaction during the pumping stage, and the leakoff increases slightly due to filtercake relaxation during the closure stage. An experimental study [28] on propagation of hydraulic fracture in an underconsolidated porous rock has shown that the hole breakdown pressure and fracture propagation pressure are much higher than that predicted by the elastic analysis.…”
Section: Poroelasticity and Filtercakementioning
confidence: 86%
“…This value is consistent with values used in other studies and with laboratory measured fluid loss data on core samples (Willson et al 1999). Elsewhere, cuttings slurry leakoff tests into highly permeable sands have suggested a leakoff coefficient of 0.004 ft/√min for slurry injection (Sirevag and Bale 1993;Moschovidis et al 1993;Willson et al 1993;Guo et al 2000). A value of 6×10 −5 ft/√min was assumed in the overlying shalier formations (Sirevag and Bale 1993;Moschovidis et al 1993;Willson et al 1993;Guo et al 2000;Willson et al 1999).…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…Over time, environmental regulatory requirements have become stricter, drilling and mud system technologies have advanced, and many companies have voluntarily adopted waste management options with more benign environmental impacts than those used in the past. Drill cuttings reinjection (DCRI) operations started in the late 1980s with small volumes of drill cuttings slurry using either tubular or annular injections (Abou-Sayed et al, 1989;Louviere and Reddoch, 1993;Malachosky et al, 1993;Sirevag and Bale, 1993;Willson et al, 1993;Moschovidis et al, 1994). However, as more experience was gained through these lower volume waste disposal operations, drill cuttings injections have been operated in several parts of the world as an economical solution for drilling waste disposal (Baker et al, 1999;Schmidt et al, 1999;Guo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The rheological characteristics of cuttings slurries have been commonly represented by a non-Newtonian power law relationship. The power law indices vary significantly (Sirevag and Bale, 1993;Willson et al, 1993Willson et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%